Evaluation of Antioxidant status in Oral Submucous Fibrosis: A Hospital Based study - Ranjit S. Ambad, Sanjay Agrawal; Ranjit S. Ambad, Sanjay Agrawal (International Journal of Innovative Research in Medical Science, 2017)
Purpose: - Measurement of activity of Glutathione peroxidase (Gpx) and Superoxide dismutase (SOD) in oral submucous fibrosis. Methods: - For the study comprising total 128 cases suffering from oral submucous fibrosis were selected. All patients were clinically and histopathologically diagnosed. A total of 100 age and sex matched healthy subjects taken as control. The circulating levels of SOD and GPx activity were assayed in the in the serum of control group and in patients with oral submucous fibrosis. Results: - Mean SOD and Gpx activity in serum were significantly decreased in oral submucous fibrosis patients as compared to control (p<0.001). Conclusion: - In the present study I concluded that the activity of SOD and Gpx were significantly decreased found in oral submucous fibrosis patients because reactive oxygen species (ROS) are generated through numerous normal metabolic processes and are needed for normal functioning of the organism. Various antioxidant enzymes like superoxide dismutase (SOD) and glutathione peroxidase (GPx) control their accumulation. Oxidative stress caused by increased free radical generation and decreased antioxidant level in the target cells and tissues has been suggested to play an important role in oral submucous fibrosis. In this study antioxidant enzyme SOD with and GPx shows positive correlation.